2020
DOI: 10.24990/injec.v5i1.273
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation Between Self-Care Behavior and The Self-Efficacy of Hypertensive Adults

Abstract: Introduction: Medication adherence is critical to succesful of hypertension control, and other effort to maintain blood pressure for hypertensive adult is lifestyle modifica­tions involving healthy eating, sodium reduction, and increased physical activity. A person’s behavior to maintain their health condition including their high blood pressure can be affected by their self-efficacy. The purpose of this study is to assess the self-care behavior of hypertensive adults to examine its relationship with the self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Participants’ ages ranged from 18 to 88 years, with a mean age of 55.64; about 67.97% of participants were female. Nearly half of the studies ( k = 10; 42%) focused on older adults ( M age > 60 year; Adiyasa & Cruz, 2020; Gee, 2005; Hu et al, 2015; Kim et al, 2020; Larki et al, 2018; Lee et al, 2007; Lee & Laffrey, 2006; Sol et al, 2011; Xie et al, 2020; Yan et al, 2012). About 21% of the selected studies ( k = 5) recruited African Americans (Gee, 2005; Kang et al, 2020; Kirkendoll et al, 2010; Mansyur et al, 2013; Warren-Findlow et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants’ ages ranged from 18 to 88 years, with a mean age of 55.64; about 67.97% of participants were female. Nearly half of the studies ( k = 10; 42%) focused on older adults ( M age > 60 year; Adiyasa & Cruz, 2020; Gee, 2005; Hu et al, 2015; Kim et al, 2020; Larki et al, 2018; Lee et al, 2007; Lee & Laffrey, 2006; Sol et al, 2011; Xie et al, 2020; Yan et al, 2012). About 21% of the selected studies ( k = 5) recruited African Americans (Gee, 2005; Kang et al, 2020; Kirkendoll et al, 2010; Mansyur et al, 2013; Warren-Findlow et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies were quantitative (k = 22, 92%), with 19 cross-sectional (79%), two longitudinal (8%), one randomized controlled trial, and two qualitative studies (8%). The sample sizes ranged from 11 (Kirkendoll et al, 2010) to 671 (Kamran Adiyasa & Cruz, 2020;Gee, 2005;Hu et al, 2015;Kim et al, 2020;Larki et al, 2018;Lee et al, 2007;Lee & Laffrey, 2006;Sol et al, 2011;Xie et al, 2020;Yan et al, 2012). About 21% of the selected studies (k = 5) recruited African Americans (Gee, 2005;Kang et al, 2020;Kirkendoll et al, 2010;Mansyur et al, 2013;Warren-Findlow et al, 2012).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In the quantitative and mixed-method studies, body weight management (29 studies 20 , 24 , 25 , 29 , 30 , 33 , 36 , 39–50 , 52 , 53 , 56–62 , 64 ) and physical exercise (22 studies 21 , 22 , 24 , 30–33 , 35 , 38 , 40–43 , 45 , 47 , 52 , 53 , 56 , 57 , 60 , 61 , 75 ) were the most reported, whereas in the qualitative studies, medication adherence and diet intake was the most reported self-care practice. In addition, a few studies described alternative self-care management methods such as stress-relieving methods (6 studies 35 , 40 , 60 , 66 , 68 , 75 ), sleep and rest (2 studies 68 , 74 ), and spiritual fulfilment was described in one study.…”
Section: Self-care and Lifestyle Managementmentioning
confidence: 99%
“…A study with the largest sample (313,714) was conducted by Nurdiantami et al 24 Sample sizes ranged from 5 to 30 participants in the qualitative studies reviewed. For study settings, in quantitative and mixed-method studies, 10 studies took place nationally, 24,41,[47][48][49][50][51]53,63,64 19 in the urban areas, 20,21,23,[31][32][33][36][37][38]40,42,[44][45][46]52,54,55,58,76 16 in rural areas, 22,[25][26][27][28][29]34,39,43,56,57,[59][60][61][62]75 and two studies in multiple settings. 30,35 For quantitative studies, four of them were conducted in urban settings, …”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation